Purchasing consultancy - Pemer, Frida (Henry Stewart Talks, 2015)
Purchasing consultancy in public and private sectors, Relational purchasing practices, Trend towards formalization, Three strategies for purchasing consultancy, Difficulties of changing purchasing practices, Dealing with the increase of political activities in organizations, New innovations in public procurement